2019
DOI: 10.3168/jds.2019-16578
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of dairy calf management practices, colostrum quality, failure of transfer of passive immunity, and occurrence of enteropathogens among Australian dairy farms

Abstract: Calf preweaning morbidity and mortality risks have been reported as high in several countries, with average values approximating 35 and 7%, respectively. However, limited data are available for calf morbidity and mortality risks on Australian dairy farms. The aims of this study were (1) to investigate current calf management practices on dairy farms in Australia and their association with herd-level morbidity and mortality using a questionnaire-based, cross-sectional study; and (2) to estimate the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 71 publications
6
78
2
1
Order By: Relevance
“…Of 268 NZ samples taken of pooled colostrum, 91 and 91% failed for TBC and CC, respectively (16). Of 221 Australian colostrum samples, 42 and 28% of samples failed on TBC and CC, respectively, with only 20% meeting both standards for immunoglobulin (>50 g/L) and microbiological quality (17), reinforcing previous Australian studies which found 42 and 6% of samples exceeded TBC and CC, respectively, with only 23% meeting all standards for TBC, CC and immunoglobulin levels (18). Previous studies examining colostrum bacteriological levels in Irish dairy herds reported 57% of 214 samples exceeding TBC and 33% exceeding CC thresholds, with significant variation between farms (9), however, there have been no published studies on colostrum hygiene levels on GB dairy farms to date.…”
Section: Introductionmentioning
confidence: 99%
“…Of 268 NZ samples taken of pooled colostrum, 91 and 91% failed for TBC and CC, respectively (16). Of 221 Australian colostrum samples, 42 and 28% of samples failed on TBC and CC, respectively, with only 20% meeting both standards for immunoglobulin (>50 g/L) and microbiological quality (17), reinforcing previous Australian studies which found 42 and 6% of samples exceeded TBC and CC, respectively, with only 23% meeting all standards for TBC, CC and immunoglobulin levels (18). Previous studies examining colostrum bacteriological levels in Irish dairy herds reported 57% of 214 samples exceeding TBC and 33% exceeding CC thresholds, with significant variation between farms (9), however, there have been no published studies on colostrum hygiene levels on GB dairy farms to date.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous reports. 11 In the current study, on average, the estimated total LW loss with a single pneumonia event was 14.6 kg ( Figure 1). This trend is in agreement with previous findings where calves with episodes of the respiratory disease had a significant reduction (8.2 kg) in carcass weight.…”
Section: Discussionmentioning
confidence: 64%
“…1,7,20 These growth rates varied depending on nutritional factors 7,27 and disease incidence. 11 A study by Johnson et al described how feeding policies and other risk factors impacted the growth rate on 492 UK calves. 36 The study reported that ADG varied between farms from 0.52 to 0.75 kg/day depending on how much milk was fed, the presence of for the fortnight prior to disease event, 1 level for the fortnight of the confirmed disease event, levels 2-4 are for the three fortnights (maximum number of fortnights until weaning assuming a calf was observed with an even on the first fortnight) after disease event fortnight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations